2010
DOI: 10.1007/s10856-010-4011-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HA released calcium ion on osteoblast differentiation

Abstract: Hydroxyapatite (HA) is a widely used calcium phosphate implant substitute and has dissolution property. Although HA has been shown a beneficial effect on osteoblast differentiation, the exact mechanism is still unclear. In the present study, we proposed that Ca(2+) released from HA activated the expression bone associated proteins, OPN and BSP, mediated by L-type calcium channel and calcium/calmodulin-dependent protein kinase (CaMK) 2 which resulted into improved osteoblast differentiation. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 23 publications
5
116
1
2
Order By: Relevance
“…An et al demonstrated that increased concentrations of Ca 2+ ions had no effect on proliferation of human dental pulp cells, but led to changes in osteogenic differentiation [21]. Similarly, Jung et al demonstrated that osteoblast differentiation was enhanced by Ca 2+ released from hydroxyapatite [22]. These findings are contradictory to our observations, which indicate that a large increase in Ca 2+ concentration (the HCM and KMC-C extracts) has a cytotoxic effect on osteoblast cells in vitro.…”
Section: -contrasting
confidence: 99%
See 1 more Smart Citation
“…An et al demonstrated that increased concentrations of Ca 2+ ions had no effect on proliferation of human dental pulp cells, but led to changes in osteogenic differentiation [21]. Similarly, Jung et al demonstrated that osteoblast differentiation was enhanced by Ca 2+ released from hydroxyapatite [22]. These findings are contradictory to our observations, which indicate that a large increase in Ca 2+ concentration (the HCM and KMC-C extracts) has a cytotoxic effect on osteoblast cells in vitro.…”
Section: -contrasting
confidence: 99%
“…Interestingly, according to the available literature, increased levels of calcium ions are considered to promote osteogenic differentiation and mineralization [21,22]. An et al demonstrated that increased concentrations of Ca 2+ ions had no effect on proliferation of human dental pulp cells, but led to changes in osteogenic differentiation [21].…”
Section: -mentioning
confidence: 99%
“…The ability to form a carbonated HA on the surface is considered to be the main aspect of CaP grafts` bioactivity [13]. The release of Ca has also positive effects on the differentiation of osteoblasts because it activates Ca-dependent protein kinases via Ca channels, leading to a higher expression of ALP, osteopontin and OC [57].…”
Section: Characterization and Preparation Of Synthetic Hamentioning
confidence: 99%
“…[54].The activation of runx2 as the most important pro-osteogenic differentiation factor via ERK1/2 pathways plays a central role in these processes [57]. In the case that other ions are a part of the HA lattice, it may have additional effects.…”
Section: Characterization and Preparation Of Synthetic Hamentioning
confidence: 99%
“…In particular, enzyme-mediated hydroxyapatite-based biomaterials have been used in animal tests and have achieved successful outcomes. One possible reason for this is that enzyme-mediated hydroxyapatite is readily soluble to body fluids due to its low crystallinity, and the release of calcium ions may cause desirable effects, such as promoting the differentiation of osteoblastic cells as reported by Jung et al 98) Enzyme-mediated hydroxyapatite-based biomaterials may become the first successful example of practical application of this technique if the biological safety of the enzymes and reagents used is guaranteed.…”
Section: Concluding Remarks and Future Outlookmentioning
confidence: 99%